ASPECTS REGARDING THE KINETIC MEASUREMENT RECOVERY OF THE BRAHLE PLEX - Florian BENEDEK (Editura Universitatii Transilvania din Brasov, 2018)
This paper presents the study of a complex pathology of the upper limb encountered on an adult patient, namely brachial plexus paresis occurred at birth. The traumatic factor acting in these cases can often be brutal or faulty obstetric maneuvers, which can reversibly or irreversibly damage the movements of the newborn's upper and lower limbs. The importance of the studied topic is that this trauma determines physical, economic, social, psychic limitations even to the dependence on another person or to the means of assistance, and may be invalid. At the beginning of the study, the research framework was established, the hypothesis was made and the anamnesis was done, the research methods and techniques were selected, the study and the research techniques were applied, the data was rec